The architecture of the Jubilee Line Extension - Bennett, David, 1948- (Thomas Telford, 2004)
David Bennett's latest book focuses on the fusion of innovative architecture and engineering on London Underground's Jubilee Line Extension. The book highlights the complexity of the engineering involved and the difficulties of creating architecture in reverse.